2017
DOI: 10.1016/j.pacs.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic signal characterization of cancer treatment response: Correlation with changes in tumor oxygenation

Abstract: Frequency analysis of the photoacoustic radiofrequency signals and oxygen saturation estimates were used to monitor the in-vivo response of a novel, thermosensitive liposome treatment. The liposome encapsulated doxorubicin (HaT-DOX) releasing it rapidly (<20 s) when the tumor was exposed to mild hyperthermia (43 °C). Photoacoustic imaging (VevoLAZR, 750/850 nm, 40 MHz) of EMT-6 breast cancer tumors was performed 30 min pre- and post-treatment and up to 7 days post-treatment (at 2/5/24 h timepoints). HaT-DOX-tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 76 publications
1
65
0
2
Order By: Relevance
“…Toi et al [39] demonstrated that the tumor associated blood vessels in a patient with IBC became visible in PA images after chemotherapy. Hysi et al [126] performed a PA imaging study at 750/850 nm on EMT-6 breast cancer tumor injected into mice to monitor the response of a thermosensitive liposome treatment. They observed the response of the treatment though PA images obtained at different time points 30 min before and after treatment up to seven days after treatment.…”
Section: Breast Cancer Treatment Monitoringmentioning
confidence: 99%
“…Toi et al [39] demonstrated that the tumor associated blood vessels in a patient with IBC became visible in PA images after chemotherapy. Hysi et al [126] performed a PA imaging study at 750/850 nm on EMT-6 breast cancer tumor injected into mice to monitor the response of a thermosensitive liposome treatment. They observed the response of the treatment though PA images obtained at different time points 30 min before and after treatment up to seven days after treatment.…”
Section: Breast Cancer Treatment Monitoringmentioning
confidence: 99%
“…Imaging of collagen phantoms, as well as imaging of mouse, pig, and human kidneys, was performed using the VevoLAZR-X system (Fujifilm VisualSonics Inc.) (56)(57)(58). This commercially available system uses an Nd:YAG laser 512 nm source through an optical parametric oscillator operating at 10 Hz pulse repetition frequency.…”
Section: Pa Imagingmentioning
confidence: 99%
“…Photoacoustic spectral features have been shown to be valuable tools in clinical applications, such as characterization of bone microstructure [20], quantification of normal and fatty livers [21], cancer diagnosis [22,23], and monitoring cancer treatment response [24]. In earlier studies we evaluated the feasibility of these features for distinguishing malignant from benign ex vivo ovaries [16,17].…”
Section: Pat Spectral Feature Extractionmentioning
confidence: 99%